Understanding virtue ethics - Hooft, Stan van, 1945- (Chesham [U.K.] : Acumen, 2006)
After presenting a broad overview of the history of virtue ethics, this work explores virtues in the context of contemporary moral theory to analyse how many intractable moral dilemmas might be overcome by responsible, virtuous agents.
Includes bibliographical references (pages 173-178) and index.
Description based on print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Virtue; Ethics; Ethics; Virtue; PHILOSOPHY / Ethics & Moral Philosophy; Electronic books